2012
DOI: 10.1016/j.jaapos.2011.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Variability of angle of deviation measurements in children with intermittent exotropia

Abstract: Background A change in the angle of deviation is often used to monitor change in severity of intermittent exotropia over time; nevertheless, thresholds for a clinically significant change in angle have not been determined. We analyzed variability due to test–retest differences and short-term variability in the condition to provide thresholds as a guide for assessing clinically significant, long-term change in angle of intermittent exotropia. Methods Twenty-six children with intermittent exotropia (median age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 13 publications
0
38
0
1
Order By: Relevance
“…For example, an intermittent deviation became manifest but the angle did not increase. The fact that Hatt et al 15 found less inter-examiner variability in their study investigating children with intermittent exodeviations suggests that the intermittent nature of some of the deviations did not affect the limits of agreement.…”
Section: Limitations Of the Studymentioning
confidence: 73%
See 1 more Smart Citation
“…For example, an intermittent deviation became manifest but the angle did not increase. The fact that Hatt et al 15 found less inter-examiner variability in their study investigating children with intermittent exodeviations suggests that the intermittent nature of some of the deviations did not affect the limits of agreement.…”
Section: Limitations Of the Studymentioning
confidence: 73%
“…Their findings suggested that a difference of 6 PD or more for esotropias measuring between 10 and 20 PD and that a difference of 12 PD for deviations measuring greater than 20 PD may be considered a true change. Hatt et al 15 examined children aged 1-13 years with intermittent exotropia. They reported threshold values for what may be considered a real change for deviations measuring 20PD or less and found values of 7PD and 3PD for near and distance fixation respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There does not appear to be a strong correlation between angle of deviation and ability to control. Test-retest data on angle of deviaton were recently reported (Hatt 2012) and at distance were 3.4 prism dioptres for angles < 20 prism dioptres and 7.2 prim dioptres for angles > 20 prism dioptres. These data provide guidelines for evaluating change in angle over time.…”
Section: Introductionmentioning
confidence: 70%
“…Improvement in PACT at distance and near were defined as a decrease of ≥8Δ and ≥13Δ, respectively, because these amounts exceed the repeatability coefficients of 7.2Δ and 12.8Δ for PACT angles larger than 20Δ at distance and near. 30 The same cutoffs for change that represent improvement were also used to determine the proportion of patients who worsened on each outcome. Binary outcomes were compared between treatment groups using exact logistic regression models adjusting for the baseline level of the outcome (two-sided p values are reported).…”
Section: Methodsmentioning
confidence: 99%